The sexually dimorphic expression of glutamate transporters and their implication in pain after spinal cord injury - Jennifer M. Colón-Mercado; Aranza I. Torrado-Tapias; Iris K. Salgado; José M. Santiago; Samuel E. Ocasio Rivera; Dina P. Bracho-Rincon; Luis H. Pagan Rivera; Jorge D. Miranda (Neural Regeneration Research)
In addition to the loss of motor function, ~60% of patients develop pain after spinal cord injury. The cellular-molecular mechanisms are not well understood, but the data suggests that plasticity within the rostral, epicenter, and caudal penumbra of the injury site initiates a cellular-molecular interplay that acts as a rewiring mechanism leading to central neuropathic pain. Sprouting can lead to the formation of new connections triggering abnormal sensory transmission. The excitatory glutamate transporters are responsible for the reuptake of extracellular glutamate which makes them a critical target to prevent neuronal hyperexcitability and excitotoxicity. Our previous studies showed a sexually dimorphic therapeutic window for spinal cord injury after treatment with the selective estrogen receptor modulator tamoxifen. In this study, we investigated the anti-allodynic effects of tamoxifen in male and female rats with spinal cord injury. We hypothesized that tamoxifen exerts anti-allodynic effects by increasing the expression of glutamate transporters, leading to reduced hyperexcitability of the secondary neuron or by decreasing aberrant sprouting. Male and female rats received a moderate contusion to the thoracic spinal cord followed by subcutaneous slow-release treatment of tamoxifen or matrix pellets as a control (placebo). We used von Frey monofilaments and the “up-down method” to evaluate mechanical allodynia. Tamoxifen treatment decreased allodynia only in female rats with spinal cord injury revealing a sex-dependent effect. The expression profile of glutamatergic transporters (excitatory amino acid transporter 1/glutamate aspartate transporter and excitatory amino acid transporter 2/glutamate transporter-1) revealed a sexual dimorphism in the rostral, epicenter, and caudal areas of the spinal cord with a pattern of expression primarily on astrocytes. Female rodents showed a significantly higher level of excitatory amino acid transporter-1 expression while male rodents showed increased excitatory amino acid transporter-2 expression compared with female rodents. Analyses of peptidergic (calcitonin gene-related peptide-α) and non-peptidergic (isolectin B4) fibers outgrowth in the dorsal horn after spinal cord injury showed an increased calcitonin gene-related peptide-α/ isolectin B4 ratio in comparison with sham, suggesting increased receptive fields in the dorsal horn. Although the behavioral assay shows decreased allodynia in tamoxifen-treated female rats, this was not associated with overexpression of glutamate transporters or alterations in the dorsal horn laminae fibers at 28 days post-injury. Our findings provide new evidence of the sexually dimorphic expression of glutamate transporters in the spinal cord. The dimorphic expression revealed in this study provides a therapeutic opportunity for treating chronic pain, an area with a critical need for treatment.